Technological literacy of students - future teachers - from the perspectives of knowledge, experience and evaluation of the importance of technology in life and education - Darjo Zuljan; Milena Valenčič Zuljan (University of Maribor Press, 2015)
Individual's participation in a technological society demands deep and critical understanding of technology and its impact on each individual, environment and society. Achieving technological literacy has become an important imperative of national policies; hence, the role of education along with adequate teachers' training has become vital. In our research, we studied technological literacy of student teachers, their experiences with technology education in primary school, their estimation of impact of technology education in primary schools and at faculties as well as their views on the role and influence of technology in individual's life and in the society.